Clinicopathological characteristics of synchronous multiple primary early esophageal cancer and risk factors for multiple lesions - Su, Jing; Wei, Shuchun; Li, Wenjie; Chen, Han; Li, Lurong; Xu, Lijuan; Zhao, Ping; Zhang, Guoxin; Yan, Jin (Frontiers in Oncology, 2023)
Background: With the development of endoscopic technology, the detection rate of synchronous multiple primary early esophageal cancer (SMPEEC) is increasing; however, the risk factors remain unclear. We aimed to assess the clinicopathological characteristics of patients with SMPEEC and investigate the risk factors contributing to the development of multiple lesions. Methods: A retrospective cohort study was conducted on 911 consecutive patients who underwent Endoscopic submucosal dissection (ESD) for primary esophageal neoplasms from January 2013 to June 2021. The patients were divided into the SMPEEC group and the solitary early esophageal cancer (SEEC) group. We compared the differences in clinicopathological characteristics between the two groups and investigated the risk factors linked to multiple lesions. Additionally, we investigated the relationship between the main and accessory lesions. Results: A total of 87 SMPEEC patients were included in this study, and the frequency of synchronous multiple lesions was 9.55% in patients with early esophageal cancer. The lesions in the SMPEEC group were mainly located in the lower segment of the esophagus (46[52.9%]), whereas those in the SEEC group were in the middle segment (412[50.0%]). The pathology type, tumor location, and circumferential rate of lesions were independent risk factors(P<0.05) for SMPEEC by logistic regression analysis. Significant positive correlations were observed between the main and accessory lesions in terms of morphologic type (r=0.632, P=0.000), tumor location(r=0.325, P=0.037)，pathologic type (r=0.299, P=0.003), and depth of invasion (r=0.562, P=0.000). Conclusion: Pathology type, tumor location, and circumferential rate of lesions were identified as independent risk factors for SMEPPC. Understanding these risk factors and the correlation between the main and accessory lesions could significantly improve the detection rate of SMPEEC.